Java : an introduction to computing - Adams, Joel; Nyhoff, Larry R.; Nyhoff, Jeffrey (Upper Saddle River, N.J. : Prentice Hall, 2001)
Provides an introduction to computer science with an object-oriented approach to Java. Teaches traditional and graphical/internet programming. Covers Object-Centered Design, Object-Oriented Design, and GUI programming. Accompanying CD-ROM includes Java compiler (JBuilder), HTML reference guide, the text's example source code and screen snaps, and a lab manual containing laboratory exercises and projects coorinated with the text
'An Alan R. Apt book.'
Includes index
Book is accompanied by one CD, entitled'Java : an introduction to computing', bearing the same call number and available at Bahagian Koleksi Media
System requirements for accompanying CD-ROM: Windows, Linux, or Solaris
Keywords: Java (Computer program language); Computer science; Object-oriented programming (Computer science); Graphical user interfaces (Computer systems)